Marketing Strategy for Maternal and Child Services in Hospitals to Enhance Patient Experience - Lialut Iftiyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the marketing strategies of maternal and child healthcare services in hospitals to enhance patient experience, emphasizing a shift from traditional promotional approaches toward the creation of a positive and empathetic patient experience. This research employs a systematic literature review of relevant studies published between 2021 and 2025, with analysis conducted through identification, selection, and thematic synthesis to determine key factors influencing patient satisfaction and loyalty. The findings indicate that the quality of interpersonal interactions and the efficiency of service processes are the primary determinants of patient experience, where factors such as staff empathy, clear communication, reduced waiting times, and well-structured service flows have a greater impact than the technical aspects of medical care. Hospitals should therefore prioritize people- and process-oriented strategies by implementing empathy training, enhancing communication effectiveness, and regularly measuring patient satisfaction, while also integrating digital services, ensuring cost transparency, and developing continuity of care programs to strengthen the patient experience holistically. This study proposes a holistic marketing framework that integrates empathy, efficiency, data-driven personalization, and environmental sustainability, highlighting a shift from a purely clinical orientation to an experiential marketing approach that places human values at the core of a hospital’s competitive advantage.